Resposta da mamoneira (Ricinus communis L., cv. Al Guarany 2002) a diferentes tensões de água no solo. - Pinto, Marília Alves Brito (2011)
With the incentive of biodiesel production in Brazil, the castor bean crop has gained importance in the agricultural scenario, mainly because its seeds have high oil content of good quality. Being considered drought resistant plant in most reports of the literature, this is a controversial aspect because under water deficit conditions low yield has been recorded. Therefore this study had the objective to evaluate the growth and development of the castor bean submitted to different soil water tensions. A greenhouse experiment was carried out with plants of the cultivar Al Guarany 2002. Plants were cultivated in pots with one tensiometer installed at the 0.15 m depth to monitor the water soil tension. The experimental design was completely randomized with three treatments and four replications: 1- water tension maintained at 0.01 MPa; 2 when the soil water tension reached 0.03 MPa, water was added to until returning 0.01 MPa; 3 when the soil water tension reached 0.06 MPa, water was added to until returning to 0.01 MPa. Between 30 and 105 days after plant emergence (DAE) plant transpiration, leaf area, plant height and stem diameter were biweekly evaluated. The time lapse to onset of flowering and height of insertion of the first raceme were evaluated. Physiological parameters such as leaf water potential, leaf firmness and stomatal resistance were measured at 105 DAE. Results show that increasing soil water tension decreased the transpiration and growth rates of the castor bean plant. The time to flowering and height of insertion of the first raceme were greater for plants submitted to lower soil water tension. The leaf water potential and leaf firmness decreased as the soil water tension decreased. As soil water tension increased the stomatal resistance increased mainly with the rise of the atmosphere evaporative demand. Keywords: transpiration, water stress, growth e development.